Synthesis, Characterization, and Biological Activity Evaluation of Thiazolidine-4-One Derivatives Derived From Schiff Bases - Karim, Hind Majed Abdel; Jabbar, Salwa Abdel Sattar (American Journal of Biomedicine and Pharmacy, 2025)
In this study, a series of novel derivatives of thiazolidin-4-one ring (H11–H15) were synthesized via the reaction of Schiff bases with thioglycolic acid in tetrahydrofuran (THF) medium. The structures of the synthesized compounds were confirmed using various spectroscopic techniques, including FT-IR, ¹H-NMR, ¹³C-NMR, and UV-Vis. The obtained spectra revealed significant changes indicating the success of the reaction and the formation of the heterocyclic ring. The antibacterial activities of the synthesized compounds were evaluated against two clinically significant bacterial strains: Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative). The results showed that compound H14 exhibited the highest activity against E. coli, whereas compound H15 showed strong activity against S. aureus, in some cases surpassing the efficacy of the reference antibiotic amoxicillin. This selective activity highlights the potential of these compounds as promising future antibiotics in combating resistance to conventional antimicrobial agents.